2022
DOI: 10.1177/10870547221132793
|View full text |Cite
|
Sign up to set email alerts
|

Familial Factors Associated With Symptom Severity in Children and Adolescents With ADHD: A Meta-Analysis and Supplemental Review

Abstract: Objective: Both genetic and environmental factors contribute to the development of ADHD, but associations between risk factors and ADHD symptom severity in affected children remain unclear. This systematic review and meta-analysis synthesizes evidence on the association between familial factors and symptom severity in children with ADHD (PROSPERO CRD42020076440). Method: PubMed and PsycINFO were searched for eligible studies. Results: Forty-three studies ( N = 11,123 participants) were meta-analyzed. Five addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
2
8
0
1
Order By: Relevance
“…The effects of family adversity, parental psychopathology, and negative parenting practices on child externalizing symptoms were small and broadly in line with previous study findings [11,13,36,43,44]. The finding that negative parenting practices have more impact on children's externalizing behaviors than do positive parenting practices is also consistent with previous study findings [19,28,32,43].…”
Section: Effects Of Familial Factors On Child Externalizing Symptomssupporting
confidence: 90%
“…The effects of family adversity, parental psychopathology, and negative parenting practices on child externalizing symptoms were small and broadly in line with previous study findings [11,13,36,43,44]. The finding that negative parenting practices have more impact on children's externalizing behaviors than do positive parenting practices is also consistent with previous study findings [19,28,32,43].…”
Section: Effects Of Familial Factors On Child Externalizing Symptomssupporting
confidence: 90%
“…The four models analyzed were statistically significant, indicating that parenting style and the form of rule-setting had a small, though significant impact on the prediction of ADHD-associated symptomatology and emotional factors. The recent meta-analysis by Jendreizik et al [ 15 ] showed that negative parenting practices (e.g., parental expression of displeasure and criticism) were consistently associated with more severe ADHD symptoms in children. However, in line with our results, they did not find positive parenting behaviors to be associated with symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…Sasser et al [ 12 ] examined the progression of ADHD symptomatology and found that it did not persist during adolescence in every case, but instead there was greater severity and persistence of symptoms in those who had more hyperactive or aggressive behaviors or whose parents used inconsistent parenting practices with little discipline. Other studies have associated ADHD symptomatology with other parenting practices based on overprotection, control, parental rejection, high levels of discipline, and low levels of parental involvement [ 13 , 14 , 15 , 16 ]. Bearing this in mind, it is worth asking to what extent parenting practices may be associated with children’s symptomatology not only at the attentional level or in terms of hyperactivity but also at the emotional level.…”
Section: Introductionmentioning
confidence: 99%
“…This elevated level of stress has a negative impact on parenting practices, child–parent relationships, parenting effectiveness and family function (Deniz Can & Ginsburg‐Block, 2016; Townshend et al., 2016). At the same time, unhealthy psychological states such as pressure, anxiety and depression generated by caregivers in the course of taking care of chronically ill children will reduce their ability to care, and even affect the treatment and rehabilitation (Jendreizik et al., 2023). Therefore, it is important to consider strategies for reducing PS among carers of children with chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%